Correction to: How do combinations of unhealthy behaviors relate to attitudinal factors and subjective health among the adult population in the Netherlands? - Charlotte M. Dieteren; Werner B. F. Brouwer; Job van Exel (BMC, 2020)
An amendment to this paper has been published and can be accessed via the original article.